2014
DOI: 10.3390/ijerph111213047
|View full text |Cite
|
Sign up to set email alerts
|

Urinary Concentrations of Toxic and Essential Trace Elements among Rural Residents in Hainan Island, China

Abstract: Background: Toxic element exposure and essential trace element consumption may have changed after the Chinese economy transformed to a market-oriented system. The objectives of this study were to measure urinary concentrations of toxic (arsenic, cadmium, lead) and essential trace (selenium, zinc, copper) elements among rural residents in Hainan, China and to examine if variations in economic development are linked to differences in toxic and trace element exposure. Methods: We conducted a questionnaire-based s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 57 publications
1
7
1
Order By: Relevance
“…The mean Cu concentration in the urine of farmers demonstrated that their exposure to this element was not problematic. The mean concentrations of Cu were lower than those reported by Inoue et al (2014) for rural residents of Hainan Island (15.1 µg L -1 ), China.…”
Section: Trace and Major Elements In Urinecontrasting
confidence: 77%
See 2 more Smart Citations
“…The mean Cu concentration in the urine of farmers demonstrated that their exposure to this element was not problematic. The mean concentrations of Cu were lower than those reported by Inoue et al (2014) for rural residents of Hainan Island (15.1 µg L -1 ), China.…”
Section: Trace and Major Elements In Urinecontrasting
confidence: 77%
“…The mean concentration of Pb (Table 3) in the urine of all farmers was within the reference concentration range (< 0.03-2.96 µg L -1 ) for the Brazilian population (Batista et al, 2009). The mean Pb concentration was lower than those found by Inoue et al (2014) in China (4.3 µg L -1 ) and White and Sabbioni (1998) in the United Kingdom (11.9 µg L -1 ) and higher than those reported in other countries, such as France (0,55 µg L -1 ) (Goullé et al, 2005), the United States (1.3 µg L -1 ), (Komaromy-Hiller, Ash, Costa, & Howerton, 2000), and Spain (1.05 µg L -1 ) (Castaño et al, 2012). According to Kosnett (2003), Pb contamination occurs due to the ingestion of contaminated food and beverages.…”
Section: Trace and Major Elements In Urinementioning
confidence: 58%
See 1 more Smart Citation
“…We targeted participants who had slightly higher urinary As concentrations and equal or slightly lower urinary Cd/Pb concentrations, compared with those in non-polluted populations. The urinary Se concentrations ( GM = 16.5 μg/g creatinine) were lower than those reported for regions in Japan ( GM = 37.5 μg/g creatinine for men and 45.7 for women [ 52 ]) or in China ( GM = 38.3 μg/g creatinine [ 53 ]), where Se deficiency is not recognized.…”
Section: Discussionmentioning
confidence: 63%
“…For example, studies in Iran and Italy have reported higher level of scalp hair elements (i.e., lead, cobalt, cadmium, copper, and zinc) in girls than in boys ( 36 , 37 ). In addition, some researchers have revealed higher blood levels of manganese, copper, arsenic, cadmium and selenium in females than males ( 38 40 ). Similar to hair and blood, higher levels of urinary cadmium in females than in males was shown ( 33 ).…”
Section: Discussionmentioning
confidence: 99%